(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2017)
This study investigates the use of viral marketing on the Internet, and assesses its effectiveness, in terms of generating potential sales, and increasing brand awareness. Many viral marketing techniques are being used to target consumers, however it has been concluded that not all techniques are being utilised in an effective way on the Internet. The general attitude towards viral marketing, from the point of view of consumers, is that the information provided in viral marketing campaigns, is useful for making purchasing decisions. This study has concluded that businesses need to use a variety of viral marketing techniques, in order to market effectively over the Internet.